(3TQM GdCQHYjf GdfhhjIs - (3GHf Objb GdYHOs; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s
(3ChdgG (B:s
(3GdMOjK GdChd Yf YeQ Hf GdNWGH bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd EfeG GdCYeGd HGdfjGJ hEfeG dcd GeQA eG fhi s
(3BNQgG (B:s
(3GdMOjK GdKGfi hGdCQHYhf Yf CfS QVi Gddg Yfg bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd jG Hf BOe Efc eG OYhJfi hQLhJfi ZaQJ dc Ydi eG cGf efc hdG CHGdi hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs